The career of Sidney Colvin: a transitional moment at the fin-de-siècle - Jessica Feather (Journal of Art Historiography, 2018)
As director of the Fitzwilliam Museum (1876–1883) and latterly as keeper of Prints and Drawings at the British Museum (1883–1912), Sidney Colvin provides us with a test-case for examining the emergent professional practice of curators at the fin-de-siècle. This article argues that Colvin’s career bears many resemblances to the models sets up by earlier nineteenth-century curators. Colvin’s career demonstrates a continuum in an emerging professional practice which involved a greater agency given to curators in relation to their superiors, standardization of procedure and organization as well as an understanding and demonstrable use of a network of other museum professionals. Yet, Colvin’s career sits on the cusp of further changes concerning curatorial practice. It would be another generation before the Courtauld Institute was established to offer art history degrees, but with his university education and employment of academically trained protégés, Colvin had already raised professional standards, suggesting the potential for a new generation of museum curators.